Current Treatment Options In Open Diaphysed Long Bone Fracture - Maghfiroh, Indah Nurul; Saputra, Ryan Dharma (Jurnal EduHealth, 2024)
Open diaphyseal long bone fractures are a serious condition that requires complex and coordinated management to prevent complications and ensure optimal recovery. This study aims to review current treatment options in the management of these fractures, with a focus on fracture stabilization techniques and wound irrigation. The research method used is a literature study, which includes a comprehensive analysis of scientific articles, systematic observations, and relevant clinical guidelines. The results show that fracture stabilization techniques such as internal and external fixation each have advantages and disadvantages, which should be considered based on the patient's specific condition. In addition, low-pressure irrigation with saline solution is preferred to prevent additional trauma to the tissue, although the use of antiseptic solutions may be beneficial in certain cases. The discussion also highlights key challenges such as the risk of infection, non-union, and soft tissue damage, as well as the importance of a multidisciplinary approach in the management of open fractures. In conclusion, effective and efficient treatment requires a deep understanding of various medical techniques, a collaborative team, and close monitoring for complications, to achieve optimal clinical outcomes.